2022
DOI: 10.18662/po/13.1/386
|View full text |Cite
|
Sign up to set email alerts
|

Сredit Agreement in Agriculture: Economic and Legal Analysis

Abstract: The main purpose of the study is a comprehensive economic and legal analysis of the loan agreement in agriculture in the conditions of formation and development of elements of post-industrial economy in Ukraine. The research methodology is based on a systematic approach using the method of cognition from abstract to concrete and special methods of economic and statistical research (comparison, grouping, detailing of final indicators, generalization), which helped to ensure the reliability of research results a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…Thus, a number of authors (Swinnen, Gow,1999;Pingali, 2001;Artemenko, 2022) in their works examine only certain groups of negative factors related to the formation of agricultural development policy as a factor in the effectiveness of public administration during the period of transformation of society. In the above-mentioned studies, the focus is primarily on the financial component of the agricultural sector and, accordingly, the threats in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a number of authors (Swinnen, Gow,1999;Pingali, 2001;Artemenko, 2022) in their works examine only certain groups of negative factors related to the formation of agricultural development policy as a factor in the effectiveness of public administration during the period of transformation of society. In the above-mentioned studies, the focus is primarily on the financial component of the agricultural sector and, accordingly, the threats in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the sources of agricultural production credit is critical for regulators and policymakers concerned with the stability of financial institutions, agricultural production, and farmer welfare (Brewer et al, 2022). It was established that the expansion of the use of the loan contract in agriculture is a necessary lever for increasing the efficiency of production, the formation and constant restoration of a competitive technological base in modern conditions, and the further development of the entire agro-industrial complex (Artemenko et al, 2022). The major obstacles for agricultural producers can be found in capital constraints caused by limited access to credit that prevent investment in production and the implementation of modern technologies (Popović et al, 2018).…”
Section: Agricultural Loans-a Literature Reviewmentioning
confidence: 99%
“…Based on the general nature of agrarian legal principles as the main principles on which the mechanism of legal regulation of agrarian relations is based, it can be concluded that the principle of ensuring the legal security of the state runs like a red thread through the entire system of agrarian law, that is, it is a kind of core-goal, on where all agricultural and legal universities are based (Artemenko et al, 2022;Bihych et al, 2022;Gibbons et al, 1994).…”
Section: Literature Reviewmentioning
confidence: 99%